A method for preparing a spin-type polyacrylic acid magnetic mesoporous carrier for nucleic acid extraction
Through the triple structural characteristics of spin polyacrylic magnetic mesoporous carrier, the problems of small adsorption capacity and slow mass transfer speed in the existing nucleic acid extraction methods are solved, and the efficient nucleic acid extraction effect is achieved, which improves the sensitivity and efficiency of nucleic acid extraction. .
Patent Information
- Application Number
- CN202310306993.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-27
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2043-03-27
AI Technical Summary
In the existing nucleic acid extraction methods, the SiO2 coating structure on the surface of SiO2@Fe3O4 magnetic beads is compact and non-porous, resulting in a small adsorption capacity and slow diffusion mass transfer speed, which cannot meet the sensitivity and efficiency requirements of the biopharmaceutical industry for nucleic acid extraction.
Using spin-based polyacrylic acid magnetic mesoporous carrier, the spin-based magnetic iron oxide nanorod-shaped carrier core, mesoporous silica structural layer and polyacrylic acid modification layer can improve the nucleic acid adsorption site and mass transfer rate to achieve nucleic acid Improved extraction efficiency.
The spin-based polyacrylic acid magnetic mesoporous carrier greatly improves the adsorption efficiency and capacity of nucleic acid through the microscopic spin structure and mesoporous structure, simplifies the binding process of nucleic acid and magnetic beads, and improves the efficiency and purity of viral nucleic acid extraction.
Smart Images

Figure CN116550303B_ABST
Abstract
Description
Technical field:
[0001] The invention relates to the technical field of nano materials and bioengineering, and in particular to a method for preparing a spin polyacrylic acid magnetic mesoporous carrier for nucleic acid extraction. Background technology:
[0002] Nucleic acid separation and purification plays an extremely important role in molecular biology research and clinical molecular diagnosis. For precious clinical samples obtained in molecular diagnosis, whether high-quality nucleic acid molecules can be extracted is the key to the subsequent correct analysis and diagnosis results. The traditional nucleic acid extraction method based on liquid phase separation requires a large amount of sample, a long separation time, is easily contaminated, has a high degradation rate, and the residual organic solvent significantly increases the residual risk of PCR inhibitors. Compared with the liquid phase extraction method, the solid phase extraction method reduces the use of organic solvents, is relatively simple to operate, has a short separation time, and the sample is not easily contaminated and degraded during the experiment. The extracted nucleic acid has a relatively high concentration and purity. Among them, magnetic micro-nanomaterial (hereinafter referred to as magnetic beads) separation and purification technology is currently the most widely used nucleic acid extraction method, and has fully realized the automation, high throughput, and rapid extraction of nucleic acids. The magnetic bead method uses nanomagnetic beads with specific functional groups (hydroxyl, carboxyl or amino) on the surface to selectively adsorb nucleic acids to achieve nucleic acid separation and purification. In the detection system, impurities such as proteins will not be adsorbed by magnetic beads. Magnetic beads can be aggregated and dispersed under a magnetic field to achieve separation of nucleic acids from impurities. Magnetic adsorption materials are the core of magnetic bead separation and purification technology. Since silicon dioxide (SiO2) has a good ability to bind nucleic acids, SiO2@Fe3O4 magnetic beads formed by SiO2-coated magnetic fluid are the most commonly used nucleic acid magnetic separation nanomaterials. However, the SiO2 coating on the surface of SiO2@Fe3O4 magnetic beads used in nucleic acid extraction kits on the market is a dense and non-porous structure, which has shortcomings such as small adsorption capacity and slow diffusion mass transfer rate. As the biopharmaceutical industry and clinical diagnosis have increasingly higher requirements for nucleic acid extraction sensitivity, extraction efficiency, extraction yield and other indicators, it is of great significance to develop new magnetic separation nanomaterials for nucleic acid extraction that are efficient, highly sensitive and can improve the mass transfer rate of the extraction process. Summary of the invention:
[0003] The present invention solves the problems existing in the prior art and provides a method for preparing a spin polyacrylic acid magnetic mesoporous carrier for nucleic acid extraction. The spin polyacrylic acid magnetic mesoporous carrier proposed by the present invention achieves the improvement of nucleic acid adsorption sites and the improvement of mass transfer rate in the nucleic acid adsorption process through the synergistic effect of a spin magnetic iron oxide nanorod carrier core, a mesoporous silica structure layer and a polyacrylic acid modification layer, thereby ultimately improving the nucleic acid extraction efficiency.
[0004] The object of the present invention is to provide a method for preparing a spin-type polyacrylic acid magnetic mesoporous carrier for nucleic acid extraction, comprising the following steps:
[0005] S1: sealing the ferric chloride aqueous solution and placing it in an oven to obtain ferric oxyhydroxide nanorods, and dispersing the ferric oxyhydroxide nanorods in water to obtain a ferric oxyhydroxide nanorod storage solution;
[0006] S2: diluting the iron oxide nanorod storage solution obtained in step S1 to a concentration of 0.0005-0.0010 g / mL to obtain an iron oxide nanorod liquid, adding urea, hexadecyltrimethylammonium bromide (CTAB), isopropanol and cyclohexane to the iron oxide nanorod liquid, and fully mixing, wherein the mass ratio of the iron oxide nanorods to urea and hexadecyltrimethylammonium bromide in the iron oxide nanorod liquid is 1:25-35:45-55, and the volume ratio of isopropanol, cyclohexane and the iron oxide nanorod liquid is 0.08-0.12:1.4-1.6:1, adding tetraethoxysilane (TEOS), the volume ratio of tetraethoxysilane to the iron oxide nanorod liquid is 0.02-0.06:1, stirring and refluxing the reaction, controlling the coating of mesoporous silica layers of different thicknesses, cooling, washing and drying, and obtaining iron oxide nanorods (FeOOH@mSiO2) coated with mesoporous silica;
[0007] S3: calcining the mesoporous silica-coated iron oxyhydroxide nanorods (FeOOH@mSiO2) obtained in step S2 in air, and then calcining and reducing them in hydrogen to obtain black mesoporous silica-coated iron oxide nanorods (Fe3O4@mSiO2);
[0008] S4: dispersing the black mesoporous silica-coated ferroferric oxide nanorods (Fe3O4@mSiO2) obtained in step S3 into anhydrous ethanol, adding aminopropyltriethoxysilane (APTES), stirring and refluxing to react, wherein the mass ratio of the black mesoporous silica-coated ferroferric oxide nanorods to aminopropyltriethoxysilane is 1:5-1:10, and the product after the reaction is magnetically separated, washed and dried to obtain amino-modified mesoporous silica ferroferric oxide nanorods (Fe3O4@mSiO2-NH2);
[0009] S5: Disperse the amino-modified mesoporous silica ferroferric oxide nanorods (Fe3O4@mSiO2-NH2) obtained in step S4 into water, add polyacrylic acid (PAA), 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) and N-hydroxysulfosuccinimide (NHS), and stir at room temperature. The mass ratio of amino-modified mesoporous silica ferroferric oxide nanorods and polyacrylic acid is 4.5-5.5:1, and the molar ratio of polyacrylic acid, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide and N-hydroxysulfosuccinimide is 1:1.4-1.6:1.4-1.6. After magnetic separation, washing and vacuum drying, a magnetic mesoporous nanomaterial loaded with polyacrylic acid, i.e., a spin-type polyacrylic acid magnetic mesoporous carrier, can be obtained.
[0010] The magnetic bead method uses nanomagnetic microspheres with specific functional groups (hydroxyl, carboxyl or amino) on the surface to selectively adsorb nucleic acids to achieve the separation and purification of nucleic acids. In the detection system, impurities such as proteins will not adsorb to the magnetic beads. The magnetic beads can be aggregated and dispersed under the magnetic field to achieve the separation of nucleic acids and impurities. Magnetic adsorption materials are the core of magnetic bead separation and purification technology. Since silicon dioxide (SiO2) has a good ability to bind nucleic acids, SiO2@Fe3O4 magnetic beads formed by SiO2-coated magnetic fluid are the most commonly used nanomaterials for magnetic separation of nucleic acids. However, the SiO2 coating on the surface of SiO2@Fe3O4 magnetic beads used in nucleic acid extraction kits on the market is a dense and non-porous structure, which has the disadvantages of small adsorption capacity and slow diffusion and mass transfer. In addition, in the step of nucleic acid adsorption, the existing magnetic bead method nucleic acid automatic extractor must promote the binding and adsorption between magnetic beads and nucleic acids through the "beating" mode, and the dispersion of the magnetic bead material has a great influence on the extraction effect.
[0011] In view of this process, the present invention provides a spin polyacrylic acid magnetic mesoporous carrier for nucleic acid extraction, and the spin polyacrylic acid magnetic mesoporous carrier improves the efficiency of nucleic acid extraction through the triple structural characteristics.
[0012] First, the iron oxide nanorod core of the spin-type polyacrylic acid magnetic mesoporous carrier provides the structural basis for the material to achieve microscopic spin, and the microscopic spin greatly improves the binding efficiency of the polyacrylic acid magnetic mesoporous carrier and nucleic acid. The microscopic morphology of the spin-type polyacrylic acid magnetic mesoporous carrier is an elliptical rod-like structure, which is shaped like a stirrer. When the spin-type polyacrylic acid magnetic mesoporous carrier dispersion is placed on a magnetic stirrer, the magnetic stirring is turned on, and the spin-type polyacrylic acid magnetic mesoporous carrier itself begins to spin microscopically, driving the dispersion to self-stir. Based on the spin mechanism of the spin-type polyacrylic acid magnetic mesoporous carrier, in the nucleic acid adsorption step, it is no longer necessary to promote the binding and adsorption between the magnetic beads and the nucleic acid through the "beating" mode. It is only necessary to provide a magnetic field transformation driving force at the bottom of the automatic extractor (magnetic stirrer principle) to make the spin-type polyacrylic acid magnetic mesoporous carrier self-stirred, fully mixed and adsorbed with the nucleic acid, effectively improving the diffusion mass transfer rate of the nucleic acid adsorption process, thereby improving the efficiency of viral nucleic acid extraction.
[0013] Second, the mesoporous silica structure layer in the spin-bonded polyacrylic acid magnetic mesoporous carrier increases the specific surface area of the magnetic carrier.
[0014] Third, the polyacrylic acid modification layer in the spin-type polyacrylic acid magnetic mesoporous carrier provides carboxyl functional groups that can specifically adsorb nucleic acids. Polyacrylic acid is coated on the surface of the mesoporous silica structure layer. The mesoporous silica structure layer further increases the modification sites of the carboxyl functional groups by increasing the specific surface area of the magnetic carrier, which greatly increases the adsorption sites of nucleic acids, and ultimately further improves the adsorption capacity of nucleic acids.
[0015] The triple structural characteristics of the spin polyacrylic acid magnetic mesoporous carrier proposed in the present invention have a synergistic effect. Through the synergistic effect of the spin magnetic iron oxide nanorod carrier core, the mesoporous silica structure layer and the polyacrylic acid modification layer, the improvement of nucleic acid adsorption sites and the improvement of mass transfer rate during nucleic acid adsorption are achieved at the same time, ultimately improving the efficiency of nucleic acid extraction.
[0016] Preferably, in step S2, the mass ratio of oxyhydroxide nanorods to urea and hexadecyltrimethylammonium bromide in the oxyhydroxide nanorod liquid is 1:30:50, and the volume ratio of isopropanol to cyclohexane to the oxyhydroxide nanorod liquid is 0.1:1.5:1.
[0017] Preferably, the specific conditions for the stirring reflux reaction in step S2 are stirring reflux at 70° C. for 15-18 hours.
[0018] Preferably, the specific steps of calcining in air and then calcining in hydrogen for reduction reaction in step S3 are: calcining in air at 500° C. for 2.5-3.5 hours, and then calcining in hydrogen for reduction at 300° C. for 3.5-4.5 hours.
[0019] Preferably, in step S4, the mass volume ratio of the black mesoporous silica-coated ferrosoferric oxide nanorods to anhydrous ethanol is 0.0005-0.0015:1.
[0020] Preferably, the specific conditions for the stirring reflux reaction in step S4 are stirring reflux reaction at 80° C. for 10-14 hours.
[0021] Preferably, in step S5, the mass ratio of the ferrosoferric oxide nanorods of the amino-modified mesoporous silica to polyacrylic acid is 5:1, and the molar ratio of polyacrylic acid, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, and N-hydroxysulfosuccinimide is 1:1.5:1.5.
[0022] The present invention also protects the spin-type polyacrylic acid magnetic mesoporous carrier prepared by the above preparation method.
[0023] The present invention also protects the application of the spin-type polyacrylic acid magnetic mesoporous carrier in nucleic acid extraction.
[0024] Preferably, the nucleic acid is a novel coronavirus nucleic acid.
[0025] Compared with the prior art, the present invention has the following advantages:
[0026] The spin-type polyacrylic acid magnetic mesoporous carrier proposed by the present invention improves the efficiency of nucleic acid extraction through triple structural characteristics. First, the iron oxide nanorod core of the spin-type polyacrylic acid magnetic mesoporous carrier provides the structural basis for the material to realize microscopic spin, and the binding efficiency of the polyacrylic acid magnetic mesoporous carrier and nucleic acid is greatly improved through microscopic spin. The microscopic morphology of the spin-type polyacrylic acid magnetic mesoporous carrier is an elliptical rod-like structure, and its shape resembles a stirrer. When the spin-type polyacrylic acid magnetic mesoporous carrier dispersion is placed on a magnetic stirrer, the magnetic stirring is turned on, and the spin-type polyacrylic acid magnetic mesoporous carrier itself begins to microscopically spin, driving the dispersion to self-stir. Based on the spin mechanism of the spin-type polyacrylic acid magnetic mesoporous carrier, in the nucleic acid adsorption step, it is no longer necessary to promote the binding and adsorption between the magnetic beads and the nucleic acid through the "beating" mode. It is only necessary to provide a magnetic field transformation driving force at the bottom of the automatic extractor (the principle of the magnetic stirrer) to make the spin-type polyacrylic acid magnetic mesoporous carrier self-stirring, fully mixing and adsorbing with the nucleic acid, effectively improving the diffusion mass transfer rate of the nucleic acid adsorption process, and thus improving the efficiency of viral nucleic acid extraction. Second, the mesoporous silica structure layer in the spin-type polyacrylic acid magnetic mesoporous carrier can increase the specific surface area of the magnetic carrier. Third, the polyacrylic acid modification layer in the spin-type polyacrylic acid magnetic mesoporous carrier provides a carboxyl functional group that can be specifically adsorbed with nucleic acids. The polyacrylic acid is coated on the surface of the mesoporous silica structure layer. The mesoporous silica structure layer further increases the modification sites of the carboxyl functional group by increasing the specific surface area of the magnetic carrier, that is, it greatly increases the adsorption sites of nucleic acids, and ultimately further improves the adsorption capacity of nucleic acids. The triple structural characteristics of the spin polyacrylic acid magnetic mesoporous carrier proposed in the present invention have a synergistic effect. Through the synergistic effect of the spin magnetic iron oxide nanorod carrier core, the mesoporous silica structure layer and the polyacrylic acid modification layer, the improvement of nucleic acid adsorption sites and the improvement of mass transfer rate during nucleic acid adsorption are achieved at the same time, ultimately improving the efficiency of nucleic acid extraction. Description of the drawings:
[0027] Figure 1 The iron oxyhydroxide nanorods prepared in Example 1 are shown in FIG.
[0028] Figure 2 The oxyhydroxide iron nanorods coated with mesoporous silica prepared in Example 1.
[0029] Figure 3 It is the spin-type polyacrylic acid magnetic mesoporous carrier prepared in Example 1. Specific implementation method:
[0030] The following examples are provided to further illustrate the present invention, rather than to limit the present invention.
[0031] Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the experimental materials and reagents herein are conventional commercial products in the art.
[0032] Example 1
[0033] A method for preparing a spin-type polyacrylic acid magnetic mesoporous carrier for nucleic acid extraction comprises the following steps:
[0034] S1. Seal the 1 mM ferric chloride aqueous solution and place it in a 90°C oven for 12 hours to obtain iron oxyhydroxide nanorods, i.e., the spin-magnetic rod-shaped carrier core, such as Figure 1 As shown, the size of the iron oxyhydroxide nanorods is about 400×50 nm. After cooling, centrifugation, washing twice with water, and dispersion in water, the iron oxyhydroxide nanorod storage solution is obtained for use.
[0035] S2, dilute the iron oxyhydroxide nanorod storage solution (containing 10 mg of iron oxyhydroxide nanorods) obtained in step S1 with water to a volume of 15 mL of the iron oxyhydroxide nanorod storage solution, add urea (0.3 g), hexadecyltrimethylammonium bromide (CTAB, 0.5 g), isopropanol (1 mL) and cyclohexane (15 mL), ultrasonically disperse and fully mix, add 600 μL of tetraethoxysilane (TEOS), stir and reflux at 70°C for 16 hours, and control the thickness of the coated mesoporous silica layer to be about 150 nm. Cool, centrifuge, wash with water, and dry to obtain iron oxyhydroxide nanorods (FeOOH@mSiO2) coated with mesoporous silica, such as Figure 2 As shown, the thickness of the mesoporous silica layer is about 150 nm, and the layer is uniformly coated on the outer layer of the iron oxyhydroxide nanorods. The size of the iron oxyhydroxide nanorods coated with the mesoporous silica is about 700×350 nm.
[0036] S3. Calcine 200 mg of mesoporous silica-coated iron oxyhydroxide nanorods (FeOOH@mSiO2) at 500°C in air for 3 hours, and then calcine and reduce them in hydrogen at 300°C for 4 hours to obtain black mesoporous silica-coated iron oxide nanorods (Fe3O4@mSiO2).
[0037] S4, disperse 100mg of black mesoporous silica-coated ferroferric oxide nanorods (Fe3O4@mSiO2) in 100mL of anhydrous ethanol, add aminopropyltriethoxysilane (APTES), stir and reflux at 80℃ for 12 hours, the mass ratio of Fe3O4@mSiO2 and APETS is 1:5, and the number of amino groups modified on the surface of the nanorods is regulated. Magnetic separation, alcohol washing three times, water washing once, and drying are performed to obtain amino-modified mesoporous silica ferroferric oxide nanorods (Fe3O4@mSiO2-NH2).
[0038] S5. Disperse 100 mg of amino-modified mesoporous silica ferroferric oxide nanorods (Fe3O4@mSiO2-NH2) into 50 mL of water, add polyacrylic acid (PAA), 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) and N-hydroxysulfosuccinimide (NHS), and stir at room temperature for 12 hours. The mass ratio of Fe3O4@mSiO2-NH2 and PAA is 5:1, and the molar ratio of PAA:EDC:NHS is 1:1.5:1.5. The product is separated by magnetic separation, washed three times with water, washed three times with ethanol, and vacuum dried to obtain a magnetic mesoporous nanomaterial loaded with polyacrylic acid (Fe3O4@mSiO2-PAA), i.e., a spin-type polyacrylic acid magnetic mesoporous carrier. Figure 3 As shown, the size of the spin polyacrylic acid magnetic mesoporous carrier is about 800×400 nm. After loading polyacrylic acid, the thickness of the mesoporous silica-polyacrylic acid outer layer structure increases slightly.
[0039] Example 2
[0040] The method is the same as Example 1, except that: in step S2, the hydroxyl iron nanorod storage solution obtained in step S1 is diluted to a concentration of 0.0005 g / mL to obtain a hydroxyl iron nanorod liquid, the mass ratio of hydroxyl iron nanorods to urea and hexadecyltrimethylammonium bromide in the hydroxyl iron nanorod liquid is 1:25:45, the volume ratio of isopropanol, cyclohexane and the hydroxyl iron nanorod liquid is 0.08:1.4:1, the volume ratio of tetraethoxysilane to the hydroxyl iron nanorod liquid is 0.02:1, and the specific conditions of the stirring reflux reaction are stirring and reflux at 70°C for 18 hours.
[0041] The specific steps of the calcination in air and then calcination reduction reaction in hydrogen in step S3 are: calcination in air at 500° C. for 3.5 hours, and then calcination reduction in hydrogen at 300° C. for 4.5 hours.
[0042] In step S4, the mass volume ratio of the black mesoporous silica-coated ferrosoferric oxide nanorods to anhydrous ethanol is 0.0005:1, the mass ratio of the black mesoporous silica-coated ferrosoferric oxide nanorods to aminopropyltriethoxysilane is 1:5, and the specific conditions for the stirring reflux reaction are stirring reflux reaction at 80° C. for 14 hours.
[0043] In step S5, the mass ratio of the ferrosoferric oxide nanorods of the amino-modified mesoporous silica to polyacrylic acid is 4.5:1, and the molar ratio of polyacrylic acid, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, and N-hydroxysulfosuccinimide is 1:1.4:1.4.
[0044] Example 3
[0045] The method is the same as Example 1, except that: in step S2, the hydroxyl iron nanorod storage solution obtained in step S1 is diluted to a concentration of 0.0010 g / mL to obtain a hydroxyl iron nanorod liquid, the mass ratio of hydroxyl iron nanorods to urea and hexadecyltrimethylammonium bromide in the hydroxyl iron nanorod liquid is 1:35:55, the volume ratio of isopropanol, cyclohexane and the hydroxyl iron nanorod liquid is 0.12:1.6:1, the volume ratio of tetraethoxysilane to the hydroxyl iron nanorod liquid is 0.06:1, and the specific conditions of the stirring reflux reaction are stirring and reflux at 70°C for 15 hours.
[0046] The specific steps of the calcination in air and then calcination reduction reaction in hydrogen in step S3 are: calcination in air at 500° C. for 2.5 hours, and then calcination reduction in hydrogen at 300° C. for 3.5 hours.
[0047] In step S4, the mass volume ratio of the black mesoporous silica-coated ferrosoferric oxide nanorods to anhydrous ethanol is 0.0015:1, the mass ratio of the black mesoporous silica-coated ferrosoferric oxide nanorods to aminopropyltriethoxysilane is 1:10, and the specific conditions for the stirring reflux reaction are stirring reflux reaction at 80° C. for 10 hours.
[0048] In step S5, the mass ratio of the ferrosoferric oxide nanorods of the amino-modified mesoporous silica to polyacrylic acid is 5.5:1, and the molar ratio of polyacrylic acid, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide, and N-hydroxysulfosuccinimide is 1:1.6:1.6.
[0049] Comparative Example 1
[0050] A method for preparing a spin-type polyacrylic acid magnetic mesoporous carrier for nucleic acid extraction comprises the following steps:
[0051] S1. Seal the 1 mM ferric chloride aqueous solution and place it in a 90°C oven for 12 hours to obtain oxyhydroxide nanorods ( Figure 1 ) is the spin magnetic rod carrier core. After cooling, centrifugation, washing twice with water, and drying for use. S2, calcining 200 mg of oxyhydroxide iron nanorods at 500°C in air for 3 hours, and then calcining and reducing in hydrogen at 300°C for 4 hours to obtain black ferrosoferric oxide nanorods.
[0052] S3, disperse 100 mg of ferroferric oxide nanorods into 100 mL of anhydrous ethanol, add aminopropyltriethoxysilane (APTES), stir and reflux at 80°C for 12 hours, the mass ratio of ferroferric oxide nanorods to APETS is 1:5, and the number of amino groups modified on the surface of the nanorods is regulated. Magnetic separation, alcohol washing three times, water washing once, and drying to obtain amino-modified ferroferric oxide nanorods.
[0053] S4, 100 mg of the amino-modified ferroferric oxide nanorods obtained in step S3 were dispersed in 50 mL of water, polyacrylic acid (PAA), 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) and N-hydroxysulfosuccinimide (NHS) were added, and stirred at room temperature for 12 hours. The mass ratio of Fe3O4@mSiO2-NH2 and PAA was 5:1, and the molar ratio of PAA:EDC:NHS was 1:1.5:1.5. The product was separated by magnetic separation, washed three times with water, washed three times with ethanol, and vacuum dried to obtain a magnetic ferroferric oxide nanorod material loaded with polyacrylic acid.
[0054] Comparative Example 2
[0055] A method for preparing a spin-type polyacrylic acid magnetic mesoporous carrier for nucleic acid extraction comprises the following steps:
[0056] S1. Seal the 1 mM ferric chloride aqueous solution and place it in a 90°C oven for 12 hours to obtain oxyhydroxide nanorods ( Figure 1 ) is the spin magnetic rod-shaped carrier core. After cooling, centrifugation, washing twice, and dispersion in water, the iron oxyhydroxide nanorod storage solution is obtained for use.
[0057] S2, dilute the iron oxyhydroxide nanorod storage solution (containing 10 mg of iron oxyhydroxide nanorods) obtained in step S1 with water to a volume of 15 mL of the iron oxyhydroxide nanorod storage solution, add urea (0.3 g), hexadecyltrimethylammonium bromide (CTAB, 0.5 g), isopropanol (1 mL) and cyclohexane (15 mL), ultrasonically disperse and fully mix, add 600 μL of tetraethoxysilane (TEOS), stir and reflux at 70°C for 16 hours. Cool, centrifuge, wash with water, and dry to obtain iron oxyhydroxide nanorods (FeOOH@mSiO2) coated with mesoporous silica, such as Figure 2 shown.
[0058] S3. Calcine 200 mg of mesoporous silica-coated iron oxyhydroxide nanorods (FeOOH@mSiO2) at 500°C in air for 3 hours, and then calcine and reduce them in hydrogen at 300°C for 4 hours to obtain black mesoporous silica-coated iron oxide nanorods (Fe3O4@mSiO2).
[0059] S4, disperse 100mg of black mesoporous silica-coated ferroferric oxide nanorods (Fe3O4@mSiO2) in 100mL of anhydrous ethanol, add aminopropyltriethoxysilane (APTES), stir and reflux at 80℃ for 12 hours, the mass ratio of Fe3O4@mSiO2 and APETS is 1:5, and the number of amino groups modified on the surface of the nanorods is regulated. Magnetic separation, alcohol washing three times, water washing once, and drying to obtain amino-modified and mesoporous silica-coated ferroferric oxide nanorods (Fe3O4@mSiO2-NH2).
[0060] Application Example 1: Application of spin-type polyacrylic acid magnetic mesoporous carrier in the extraction of 2019-nCov pseudovirus RNA (automatic extraction)
[0061] The spin-type polyacrylic acid magnetic mesoporous carrier material prepared in Example 1 was dispersed in water at a concentration of 40 mg / mL. Take a 96-well plate, add 600 μL of washing solution to the 4th and 10th columns, add 100 μL of elution solution to the 6th and 12th columns, and add 20 μL of proteinase K, 20 μL of the above-mentioned spin-type polyacrylic acid magnetic mesoporous carrier material aqueous dispersion, 200 μL of the new crown 2019-nCov pseudovirus sample (concentration of 5×10 4 The sample nucleic acid was extracted quickly using an automatic nucleic acid extractor. The mixing time of the running program was set to 4, 1, 1, 1 min, the number of magnetic absorption was 1, 1, 1, 0, and the temperature was 70 ° C, room temperature, 70 ° C, room temperature. After the program was completed, the eluate was added to the fluorescent quantitative PCR reagent for quantitative amplification, and the nucleic acid extraction effect of the spin polyacrylic acid magnetic mesoporous carrier material and the original magnetic bead dispersion (commercially available magnetic beads) of the kit was compared according to the results.
[0062] The magnetic bead method for extracting COVID-19 nucleic acid refers to the extraction process described in the instructions for commercially available nucleic acid extraction or purification reagent products (Guangdong-Suizhou Medical Equipment No. 20170583; Guangzhou Daan Gene Co., Ltd.).
[0063] The fluorescent PCR nucleic acid detection process refers to the extraction process described in the instructions of the commercially available nucleic acid detection kit product (National Medical Device Registration No. 20203400749; Guangzhou Daan Gene Co., Ltd.).
[0064] Table 1 shows the results of nucleic acid extraction of the 2019-nCov pseudovirus (automatic extraction). The results show that the spin-type polyacrylic acid magnetic mesoporous carrier material dispersion can be used normally in the 2019-nCov pseudovirus RNA extraction experiment, and its nucleic acid extraction performance is equivalent to the original dispersion containing magnetic beads in the nucleic acid extraction kit.
[0065] Table 1. Results of nucleic acid extraction of 2019-nCov pseudovirus (automatic extraction)
[0066]
[0067] At the same time, the polyacrylic acid loaded magnetic ferroferric oxide nanorod material prepared in Comparative Example 1 and the amino-modified and mesoporous silica-coated ferroferric oxide nanorods prepared in Comparative Example 2 were dispersed in water at a concentration of 40 mg / mL, and nucleic acid was extracted according to the above extraction method.
[0068] The nucleic acid extraction effects of the spin polyacrylic acid magnetic mesoporous carrier material prepared in Example 1, the polyacrylic acid-loaded magnetic ferroferric oxide nanorod material prepared in Comparative Example 1, and the amino-modified and mesoporous silica-coated ferroferric oxide nanorods prepared in Comparative Example 2 are shown in Table 2.
[0069] Table 2 shows the results of nucleic acid extraction of the new coronavirus 2019-nCov pseudovirus (automatic extraction). The results show that the spin polyacrylic acid magnetic mesoporous carrier material dispersion (ie, Example 1) and the magnetic iron oxide nanorod dispersion loaded with polyacrylic acid (ie, Comparative Example 1) can be used normally in the new coronavirus 2019-nCov pseudovirus RNA extraction experiment, but the extraction effect of the spin polyacrylic acid magnetic mesoporous carrier material dispersion is better than that of the magnetic iron oxide nanorod dispersion loaded with polyacrylic acid, and the amino-modified and mesoporous silica-coated iron oxide nanorod dispersion cannot be used normally in the new coronavirus 2019-nCov pseudovirus RNA extraction experiment, and the nucleic acid extraction performance of the magnetic iron oxide nanorod dispersion loaded with polyacrylic acid (Comparative Example 2) is far worse than that of the spin polyacrylic acid magnetic mesoporous carrier material dispersion.
[0070] Table 2 New crown 2019-nCov pseudovirus nucleic acid extraction results (automatic extraction)
[0071]
[0072] Application Example 2: Application of spin-type polyacrylic acid magnetic mesoporous carrier in the extraction of 2019-nCov pseudovirus RNA (manual extraction)
[0073] The spin-type polyacrylic acid magnetic mesoporous carrier material prepared in Example 1 of the present invention was dispersed in water at a concentration of 40 mg / mL. Take a 96-well plate, add 600 μL of washing solution to the 4th and 10th columns, add 100 μL of elution solution to the 6th and 12th columns, and add 20 μL of proteinase K, 20 μL of the aqueous dispersion of the spin-type polyacrylic acid magnetic mesoporous carrier material, and 200 μL of the new crown 2019-nCov pseudovirus sample (concentration of 5×10 4 The manual extraction method was used to extract nucleic acid from the samples quickly, which mainly included three steps: binding-washing-elution. The adsorption, washing and elution times were 4, 1 and 1 min, respectively. During each step, a magnetic stirrer (350 rpm) was placed under the 96-well plate to make the spin-type polyacrylic acid magnetic mesoporous carrier self-stirred and fully mixed with the nucleic acid. After each step, magnetic separation was performed before the next step. After the extraction, the eluate was added to the fluorescent quantitative PCR reagent for quantitative amplification, and the nucleic acid extraction effect of the spin-type polyacrylic acid magnetic mesoporous carrier material and the original magnetic bead dispersion (commercially available magnetic beads) of the kit were compared according to the results.
[0074] The nucleic acid extraction related reagents used in this application example, including washing solution, elution solution, proteinase K, cleavage binding solution and original magnetic bead dispersion solution, are all taken from commercially available nucleic acid extraction or purification reagent products (Guangzhou Medical Equipment No. 20170583; Guangzhou Daan Gene Co., Ltd.).
[0075] The fluorescent PCR nucleic acid detection process refers to the extraction process described in the instructions of the commercially available nucleic acid detection kit product (National Medical Device Registration No. 20203400749; Guangzhou Daan Gene Co., Ltd.).
[0076] Table 3 shows the results of nucleic acid extraction of the 2019-nCov pseudovirus (manual extraction). The results show that the spin-polyacrylic acid magnetic mesoporous carrier material dispersion can be used normally in the manual extraction experiment of the 2019-nCov pseudovirus RNA. At room temperature and when the driving force of the magnetic field transformation is provided, the spin-polyacrylic acid magnetic mesoporous carrier material self-stirs through microscopic spin, which improves the extraction efficiency of viral nucleic acid. Its nucleic acid extraction performance is better than the original dispersion containing magnetic beads in the nucleic acid extraction kit. In addition, the manual extraction effect of the spin-polyacrylic acid magnetic mesoporous carrier material dispersion is also better than the automatic extraction effect of the original dispersion containing magnetic beads in the nucleic acid extraction kit.
[0077] Table 3 2019-nCov pseudovirus nucleic acid extraction results (manual extraction)
[0078]
[0079] The viral nucleic acid extraction and purification method based on the spin polyacrylic acid magnetic mesoporous carrier of the present invention is not inferior to commercially available magnetic bead products in terms of separation efficiency and nucleic acid yield.
[0080] The description of the above embodiments is only used to help understand the technical solution and core ideas of the present invention. It should be pointed out that for technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principles of the present invention. These improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. Application of spin-type polyacrylic acid magnetic mesoporous carrier in nucleic acid extraction, characterized in that: The method for preparing the spin-type polyacrylic acid magnetic mesoporous carrier comprises the following steps: S1: sealing the ferric chloride aqueous solution and placing it in an oven to obtain ferric oxyhydroxide nanorods, and dispersing the ferric oxyhydroxide nanorods in water to obtain a ferric oxyhydroxide nanorod storage solution; S2: diluting the iron oxide storage liquid obtained in step S1 to a concentration of 0.0005-0.0010 g / mL to obtain an iron oxide nanorod liquid, adding urea, hexadecyltrimethylammonium bromide, isopropanol and cyclohexane to the iron oxide nanorod liquid, and fully mixing, wherein the mass ratio of the iron oxide nanorods to urea and hexadecyltrimethylammonium bromide in the iron oxide nanorod liquid is 1:25-35:45-55, and the volume ratio of isopropanol, cyclohexane and the iron oxide nanorod liquid is 0.08-0.12:1.4-1.6:1, adding tetraethoxysilane, and the volume ratio of tetraethoxysilane to the iron oxide nanorod liquid is 0.02-0.06:1, stirring and refluxing to react, controlling the coating of mesoporous silica layers of different thicknesses, cooling, washing with water, and drying to obtain iron oxide nanorods coated with mesoporous silica; S3: calcining the mesoporous silica-coated iron oxyhydroxide nanorods obtained in step S2 in air at 500° C. for 2.5-3.5 hours, and then calcining and reducing in hydrogen at 300° C. for 3.5-4.5 hours to obtain black mesoporous silica-coated iron oxide nanorods; S4: dispersing the black mesoporous silica-coated ferroferric oxide nanorods obtained in step S3 into anhydrous ethanol, adding aminopropyltriethoxysilane, stirring and refluxing the reaction, wherein the mass ratio of the black mesoporous silica-coated ferroferric oxide nanorods to aminopropyltriethoxysilane is 1:5-1:10, and the mass volume ratio of the black mesoporous silica-coated ferroferric oxide nanorods to anhydrous ethanol is 0.0005-0.0015:1, and the reaction product is magnetically separated, washed and dried to obtain amino-modified mesoporous silica ferroferric oxide nanorods; S5: Disperse the amino-modified mesoporous silica ferroferric oxide nanorods obtained in step S4 into water, add polyacrylic acid, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and N-hydroxysulfosuccinimide, and stir at room temperature. The mass ratio of the amino-modified mesoporous silica ferroferric oxide nanorods and polyacrylic acid is 5:1, and the molar ratio of polyacrylic acid, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide and N-hydroxysulfosuccinimide is 1:1.5:1.
5. After magnetic separation, washing and vacuum drying, the magnetic mesoporous nanomaterial loaded with polyacrylic acid, i.e., a spin-type polyacrylic acid magnetic mesoporous carrier, can be obtained.
2. The use according to claim 1, characterized in that: In step S2, the mass ratio of the oxyhydroxide nanorods to urea and cetyltrimethylammonium bromide in the oxyhydroxide nanorod liquid is 1:30:50, and the volume ratio of isopropanol to cyclohexane to the oxyhydroxide nanorod liquid is 0.1:1.5:
1.
3. The use according to claim 1 or 2, characterized in that: The specific conditions of the stirring reflux reaction in step S2 are stirring reflux at 70° C. for 15-18 hours.
4. The use according to claim 1, characterized in that: The specific conditions of the stirring reflux reaction in step S4 are stirring reflux reaction at 80° C. for 10-14 hours.
Citation Information
Patent Citations
Porous Fe3O4 / Fe / SiO2 core-shell nanorod absorbing high-frequency electromagnetic waves and a preparation method
CN101514282A
Single-stranded DNA aptamer modified SiO2 / Fe3O4 magnetic microsphere preparation method
CN103990423A
High-density carboxyl modified magnetic microspheres and preparation method thereof
CN106237947A